The impact of government interventions during the COVID-19 turmoil on borsa Istanbul - TAN, ÖMER FARUK; CEBECİ, YASİN; GÜNEŞ, NECATİ (My University, 2022)
COVID-19, which emerged as of the end of December 2019, proceeded to spread all over the world. On March 11, 2020, the World Health Organization (WHO) declared the disease a pandemic and warned countries to take certain precautions. While governments were taking restrictive measures, they also tried to support the economy. This research analyzes the impact of the Turkish government’s interventions against COVID-19 on Borsa Istanbul for the period between March 10, 2020 and April 17, 2020 applying the pooled OLS. The stringency index, containment and health index, and economic support index are used to evaluate the government’s responses to the pandemic. According to the findings, the increase in the number of cases negatively affects stock market returns. While social distancing measures taken by the government have a negative impact on stock returns, containment and healthcare policies and economic support packages have a positive effect on stock returns. Lastly, the interaction of the growth in confirmed cases with stringency index, containment and health index and economic support index are respectively examined. The findings are not significant as investors apparently expect that the social distancing measures, healthcare policies, and economic support packages are not adequate to control the pandemic.

Aralık ayı sonu itibariyle ortaya çıkan COVID-19 daha sonra hızla tüm dünyaya yayılmıştır. 11 Mart 2020’de Dünya Sağlık Örgütü (WHO) hastalığın salgın olduğunu ilan ederek ülkeleri bazı önlemler almaları konusunda uyarmıştır. Bu nedenle hükümetler kısıtlayıcı önlemler alırken, bir yandan da ekonomiyi desteklemeye çalışmışlardır. Bu araştırma, 10 Mart 2020 - 17 Nisan 2020 tarihleri arasında COVID19’a karşı Türk hükümetinin almış olduğu önlemlerin Borsa İstanbul üzerindeki etkisini En Küçük Kareler Yöntemi ile analiz etmektedir. Sıkılık endeksi, muhafaza ve sağlık endeksi ve ekonomik destek endeksi, hükümetin salgına müdahalelerini değerlendirmek için kullanılmıştır. Bulgulara göre vaka sayısındaki artış borsa getirilerini olumsuz etkilemektedir. Hükümetin almış olduğu sosyal mesafe önlemleri borsa getirilerini olumsuz etkilerken, muhafaza ve sağlık politikaları ile ekonomik destek paketleri ise borsa getirileri üzerinde olumlu etki oluşturmaktadır. Son olarak vakalardaki artışın sıkılık endeksi, muhafaza ve sağlık endeksi ve ekonomik destek endeksi ile etkileşimi sırasıyla incelenmiştir. Yatırımcıların sosyal mesafe önlemlerinin, muhafaza ve sağlık politikalarının ve ekonomik destek paketlerinin pandemiyi kontrol altına almak için yeterli olmadığına yönelik beklentilerinden dolayı sonuçlar anlamlı çıkmamıştır.
COVID-19 çalkantısı sırasında hükümet müdahalelerinin borsa İstanbul üzerindeki etkisi
Keywords: Sosyal ve Beşeri Bilimler; Finans Ekonomisi; Social Sciences and Humanities; Financial Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; COVID-19; Borsa Istanbul; financial markets; stringency index; economic support index; Borsa İstanbul; finansal piyasalar; sıkılık endeksi; ekonomik destek endeksi